Geometric and material constraints in parametric modelling: the design to fabrication process - Pitts, G.; Datta, Sambit (Taiwan Association of Digital Media Design, 2009)
Parametric modelling, commonly used in the automotive and aerospace industries, has recently been adopted in the architecture and construction fields. The ability to design small repeatable components and apply them to a larger governing surface geometry is one area of parametric modelling that has great design potential. This two level modelling control, of component and overall surface, can allow designers to explore new types of form generation subject to parametric constraints. This paper reports on the design to fabrication process using repeatable components over a governing or carrier surface. The paper reports on our study of the requirements and possible solutions for successfully controlling a repeatable element, known as a Representative Volumetric Element (RVE), using geometric parameters of a larger governing surface geometry and material properties. This modelling process, coupled with Rapid Manufacturing (RM) and Computer Numerically Controlled (CNC) machines has the potential to significantly reduce the interface between design and fabrication.